2020
DOI: 10.5222/head.2020.032
|View full text |Cite
|
Sign up to set email alerts
|

Determination of The Relationship Between Perception of Nursing Quality and Satisfaction Status of Patiens Hospitalized in Surgical Services

Abstract: Aim: This study aimed to determine the relationship between the perception of nursing care quality and the satisfaction level of patients hospitalized in surgical services. Method: The sample of this descriptive, correlational study comprised 224 patients who were hospitalized and had undergone surgical intervention. A patient information form, the Caring Behaviour Inventory-24 and the Newcastle Satisfaction Scale from Nursing Care Scale were used to collect the data. The data were evaluated by number, percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Therefore, nurses are the leading source for patients to obtain information and responses to their questions. In the literature, in studies in which satisfaction with nursing is evaluated, the mean scale score ranges between 67.82 ± 16.13 and 76.59 ± 15.11 (9,(22)(23)(24). In the present study, the mean score regarding satisfaction with nursing was 70.53 ± 16.27, which suggests that the participating women who underwent cesarean section were generally satisfied with nursing care.…”
Section: Satisfaction With Nursing Care Of Women Who Give Birth By Ce...supporting
confidence: 48%
“…Therefore, nurses are the leading source for patients to obtain information and responses to their questions. In the literature, in studies in which satisfaction with nursing is evaluated, the mean scale score ranges between 67.82 ± 16.13 and 76.59 ± 15.11 (9,(22)(23)(24). In the present study, the mean score regarding satisfaction with nursing was 70.53 ± 16.27, which suggests that the participating women who underwent cesarean section were generally satisfied with nursing care.…”
Section: Satisfaction With Nursing Care Of Women Who Give Birth By Ce...supporting
confidence: 48%
“…38, indicating a high level of satisfaction with all dimensions of nursing care. Similarly, the study of Kersu et al on surgical patients found that the participants were highly satisfied with the nursing care (32). The study of Yeşil et al on intensive care patients also found high level of patient satisfaction (33).…”
Section: Resultsmentioning
confidence: 90%
“…Positive correlation between the ICA and the NSNS scores in our study indicated that the satisfaction of the participants with nursing care increased as they believed that their individuality was supported through specific nursing interventions. The study of Kersu et al found a positive and significant correlation between the perceptions about and the patient satisfaction with the nursing care (32). The study of Tekin and Yıldız Fındık on orthopedic surgery patients in Turkey also found a positive correlation between satisfaction and the level of awareness about nursing interventions (26).…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, an increase in the quality of patient care has a positive effect on the patient's recovery process. The most important indicator of the quality of care is patient satisfaction, the accord between the patient's expectations and the care received [9]. In addition, it has been reported that a patient who is satisfied with the health care given is affected positively by the treatment, and this shortens their hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when examining studies on the determination of patient satisfaction with nursing care, it was noted that there were different conclusions about the relationship between patient satisfaction and patient characteristics [12][13][14]. Along with this, in the literature, there are studies on determining the levels of patient satisfaction with nursing care [9,10,15]; however, there are no studies on care satisfaction among patients with Covid-19.…”
Section: Introductionmentioning
confidence: 99%